Professional Development of a Beginner Teacher of a Higher Educational Establishment - Valentyna Gladkova; Oleksandr Livshun (Pedagogical Discourse, 2015)
The peculiarities of professional development of a beginner teacher of a higher educational establishment have been examined in the article. The comparative analysis of scientific works of foreign and Ukrainian scientists from the point of view of professional development of teachers shows that the problems of professional development of young teachers of comprehensive school are fundamentally researched. And the question of professional development of beginner teachers in higher educational establishment needs a serious attention from modern scientists. The quality of modern higher education is estimated by the following factors: the quality of research and teaching staff and their motivation, state of educational equipment in an educational establishment, the quality of teaching programs, the quality of students, the quality of infrastructure, the quality of knowledge, innovative activity of the administration, implementation of process innovations, competitiveness of university graduates in the labor market and their achievements, etc.Among these factors the most important is the quality of research and teaching staff in higher educational establishments. The high social significance of a teacher’s profession and its prevalence make it necessary to study the mechanisms of professional development and further professional self-realization of beginner teachers.We can conditionally single out such stages in the professional development of a teacher: adaptation, professionalization, professional skills. Two groups of work forms with beginner teachers are used in Ukraine today in order to enhance their professional competence and help them go along a difficult way of development, they are: traditional and innovative forms.To organize the work with this category of scientific and pedagogical staff the model of their professional development and the methodological materials to provide it have been proposed.